2018
DOI: 10.1016/j.neuron.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Population Mechanism for Rapid Learning

Abstract: SUMMARY Long-term learning of language, mathematics, and motor skills likely requires cortical plasticity, but behavior often requires much faster changes, sometimes even after single errors. Here, we propose one neural mechanism to rapidly develop new motor output without altering the functional connectivity within or between cortical areas. We tested cortico-cortical models relating the activity of hundreds of neurons in the premotor (PMd) and primary motor (M1) cortices throughout adaptation to reaching mov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 64 publications
(107 reference statements)
6
147
0
Order By: Relevance
“…This seems unlikely given that we observed a substantial proportion of neurons that were active during both contexts. Nonetheless, we addressed this issue following a similar procedure to Perich et al (2018). We summed the absolute value of the weights from the top-ten ipsilateral (wipsi) and contralateral (wcontra) principal components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems unlikely given that we observed a substantial proportion of neurons that were active during both contexts. Nonetheless, we addressed this issue following a similar procedure to Perich et al (2018). We summed the absolute value of the weights from the top-ten ipsilateral (wipsi) and contralateral (wcontra) principal components.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the subspaces related to the contralateral limb may not be fixed. M1 activity remains in the same subspace during motor learning (Golub et al, 2018; Perich et al, 2018; Vyas et al, 2018), and during reaching tasks with different load conditions (Gribble and Scott, 2002; Gallego et al, 2018) and initiation cues (Lara et al, 2018). However, Miri et al (2017) demonstrated that activity during locomotion and reaching occupied orthogonal subspaces that may allow motor cortex to engage separate spinal circuits for each behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, changes in these regions following learning (Mandelblat-Cerf et al, 2011;Paz et al, 2003;Perich et al, 2018) may partially reflect changes in motor plans driven by such processes. Future work could probe the interactions between these two systems, which, neuroanatomically could be sustained by reciprocal connections between the basal ganglia and the cerebellum (Bostan and Strick, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cortical representations acquired slowly over time are also essential in guiding future fast learning, which usually relies on prior knowledge and existing schemata such as when learning associations between known elements or novel words (Tse et al, 2007(Tse et al, , 2011Hebscher et al, 2019). Thus, one should keep in mind that fast and slow cortical dynamics are closely intertwined as exemplified in tasks necessitating high levels of cognitive flexibility (Pasupathy and Miller, 2005;Tse et al, 2007;Durstewitz et al, 2010;Siniscalchi et al, 2016;Perich et al, 2018;Remington et al, 2018;Rikhye et al, 2018).…”
Section: Reconstructing Fast Learning In Neuronal Network Fast Learnmentioning
confidence: 99%